Роль некоторых компонентов значения слова в создании образности - Виноградов, М. Ф. (Kalbotyra, 1990)
The paper has an aim to show that the stylistic meaning of a word in a poetic text is determined to a very large degree by the specific interaction of its denotative and connotative components.A linguistic approach to imagery helps not only to understand how a word in a poetic language turns out to be an image and to establish different types of imagery itself but also to provide sufficient data for a stylistically impeccable classification or language means and stylistic devices.